Variation in muscle activity among office workers when using different information technologies at work and away from work - Ciccarelli, Marina; Straker, Leon; Mathiassen, Svend; Pollock, Clare (Sage Publications, Inc., 2013)
Objective: To determine differences in muscle activity amplitudes and variation of amplitudes when using different information and communication tech¬nologies (ICT). Background: Office workers use different ICT to perform tasks. Upper body musculoskeletal complaints are frequently reported by this occupational group. Increased muscle activity and insufficient variation are potential risk factors for musculoskeletal complaints. Method: Muscle activity of right and left upper tra¬pezius and right wrist extensor muscle bundle (exten¬sor carpi radialis longus and brevis) of 24 office workers (performing their usual tasks requiring different ICT at work and away from work) were measured continu¬ously over 10 to 12 hours. Muscle activity variation was quantified using two indices, amplitude probability distri¬bution function and exposure variation analysis. Results: There was a trend for electronics-based New ICT tasks to involve less electromyography (EMG) variation than paper-based Old ICT tasks. Performing Com¬bined ICT tasks (i.e., using paper- and electronics-based ICT simultaneously) resulted in the highest muscle activ-ity levels and least variation; however, these Combined ICT tasks were rarely performed. Tasks involving no ICT (Non-ICT) had the greatest muscle activity variation. Conclusion: Office workers in this study used vari¬ous ICT during tasks at work and away from work. The high EMG amplitudes and low variation observed when using Combined ICT may present the greatest risk for musculoskeletal complaints, and use of Combined ICT by workers should be kept low in office work. Breaking up combined, New, and Old ICT tasks, for example, by interspersing highly variable Non-ICT tasks into office workers’ daily tasks, could increase overall muscle activity variation and reduce risk for musculoskeletal complaints.